2020
DOI: 10.21203/rs.3.rs-35593/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Stagewise Resolution of Temperature-Dependent Embryonic and Postembryonic Development in the Cowpea Seed Beetle Callosobruchus Maculatus (F.)

Abstract: Background The thermal plasticity of life-history traits receives wide attention in the recent biological literature. Of all the temperature-dependent traits studied, developmental rates of ectotherms are especially often addressed, and yet surprisingly little is known about embryonic responses to temperature, including changes in the thermal thresholds and thermal sensitivity during early development. Even postembryonic development of many cryptically living species is understood superficially at best. Result… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Hence, it was found that the egg samples treated after 15–18 h (after it was laid/oviposition) were more sensitive to CP treatment than the other two samples. Since eggs will be in two nuclei stages with a wet outer layer between 0 and3 h after oviposition (Kutcherov, 2020), they showed better resistance to CP treatment as compared to eggs that were in the process of developing embryo (15–18 h old) (de Sá et al, 2014). In contrast, the eggs that were more than 36 h old have shown more resistance to CP treatment as the embryogenesis process already produced an embryo inside the eggs.…”
Section: Resultsmentioning
confidence: 99%
“…Hence, it was found that the egg samples treated after 15–18 h (after it was laid/oviposition) were more sensitive to CP treatment than the other two samples. Since eggs will be in two nuclei stages with a wet outer layer between 0 and3 h after oviposition (Kutcherov, 2020), they showed better resistance to CP treatment as compared to eggs that were in the process of developing embryo (15–18 h old) (de Sá et al, 2014). In contrast, the eggs that were more than 36 h old have shown more resistance to CP treatment as the embryogenesis process already produced an embryo inside the eggs.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, we observed that, in captivity, M. ursulus tends to suffer earlier mortality when smaller acorns are provided as a food source from late June to early July (K. Hirayama and K. Mizo, personal observation). Kutcherov (2020) reported that larval and pupal developmental rates significantly increased with temperature in the cowpea seed beetle Callosobruchus maculatus . Based on these observations, we assumed that higher temperatures in June would probably promote the earlier emergence of M. ursulus adults, which may thereby lead to a phenological mismatch between their sap‐sucking behavior and the growth of Q. serrata acorns.…”
Section: Discussionmentioning
confidence: 99%